(untitled) (Journal of Nepal Chemical Society, 2021)
The present study was carried out to assess the contamination of heavy metals in indoor household dust of Kathmandu, Nepal, and its adverse effect on the indoor environment and human health. The concentrations of four heavy metals (Cd, Cr, Ni, and Pb) in a total of ninety-three (N = 93) indoor dust samples collected from four different types of land use zones viz., commercial, heavy traffic, residential, and control (undisturbed) of Kathmandu were determined by the flame atomic absorption spectrophotometer (FAAS). The mean concentrations of Cd, Cr, Ni, and Pb in indoor dust samples over the study zones were 0.89, 158.1, 113.3, and 65.3 mg kg−1, respectively. The land use zones showed the various degree of metal contamination in indoor dust ranging from moderate to considerable level. PLI showed a high pollution load in the monitored locations, indicating an alarming condition and the urgent need for immediate remedial actions. Hazard quotient (HQ) values indicated ingestion as the major pathway of indoor dust heavy metal exposure to children while the inhalation pathway remained dominant in adults. Hazard index (HI) values showed no probable non-carcinogenic risk of the heavy metals present in the indoor dust of Kathmandu. For carcinogenic health risk, TLCR values were found within the acceptable safe limit indicating no cancer risk for both the receptor groups.